Assessment of copper and zinc recovery from MSWI fly ash in Guangzhou based on a hydrometallurgical process. (June 2018) - Tang, Jinfeng; Su, Minhua; Zhang, Hongguo; Xiao, Tangfu; Liu, Yu; Liu, Yifan; Wei, Lezhang; Ekberg, Christian; Steenari, Britt-Marie
Highlights: A new hydro-recycling process of Cu and Zn from MSWI fly ash was evaluated. 95% of Cu and 61% of Zn were recovered in this pilot scale system. A scenario was developed based on the process for fly ash treatment in Guangzhou. Economic analysis shows combing metals recycling and local disposal as best option. The hydrometallurgical process could be alternative for industrial application. Abstract: Fly ash commonly accumulates a significant amount of heavy metals and most of these heavy metals are toxic and easily leached out to the environment, posing risks to human health. Thus, fly ash has been classified as a type of hazardous waste and requires proper treatment before disposal in specific landfill sites for hazardous waste. In this study, a hydrometallurgical process developed to recover copper and zinc performed in pilot scale close to industrial scale followed by a landfill compliance leaching test of the ash residue is evaluated. LIX860N-I and Cyanex 572 gave high selectively for extractions, a yield efficiency of 95% and 61% was achieved for copper and zinc respectively. Results of pilot experiments reveals that the combining metal recovery/recycling and landfill disposal of the ash residue in a local regular landfill was demonstrated to be a technically and economically effective strategy. Specifically, the economic and environmental aspects of a scenario, in which the fly ash generated in Guangzhou is processed were systematically assessed. the assessment results show that a 7.15 million US$ of total expense reduction, a less energy cost of 19k GJ as well as 2100 tons less CO2 emissions could be achieved annually comparing to the current alternative, direct disposal of the fly ash as hazardous waste. The results reveal that the hydrometallurgical process has industrial application potential on both economic and environmental aspects and further optimization of the process can give more accurate assessment of the cost and environment effect. In addition, leaching tests and evaluation of solid residue according to the regulations specific to the country should be studied in future.